Multi-Language Telephony Speech Data Collection and Annotation - Dias, J. (Proc. Propor 2008 Special Session (Computational Processing of the Portuguese Language)- Applications of Portuguese Speech and Language Technologies, 2008)
In this paper we detail MLDC´s platform and tools appropriate for multi-language telephony speech data collection, which is named Speech International Program - SIP. The paper focuses in the proposed system architecture and details the series of developed tools that will effectively enable a large telephony data